Environmental pollution and existing regulations : a review analysis / Nur Afrina Qistina Ahmad Halmi and Zulhabri Ismail - Nur Afrina Qistina, Ahmad Halmi; Zulhabri, Ismail (Universiti Teknologi MARA, Perak, 2017)
Construction industry despite being the important industry in generating economy, the increased number ofpollution cases from construction projects in Malaysia is alarming and becoming one of the environmental issues. Although actions have been taken, there is no indication ofa reduction of cases. Moreover, there is a need to revisit the existing laws pertaining to pollution. This paper presents a review on the environmental pollution and existing regulations in Malaysia. Furthermore, analysis of court cases on pollution is presented. The paper further identifies the issues on construction pollution and the gap in the existing legislations. The findings may be used as a platform for more extensive scholarly research in the stated area.